Acupuncture Combined With Emotional Therapy of Chinese Medicine Treatment for Improving Depressive Symptoms in Elderly Patients With Alcohol Dependence During the COVID-19 Epidemic - Zhao, Fazheng; Tong, Xin; Wang, Changqing (Frontiers in Psychology, 2021)
Objective: We aimed to analyze the characteristics and psychological mechanism of depressive symptoms in elderly patients with alcohol dependence under the COVID-19 epidemic and to observe the effect of acupuncture combined with emotional therapy of Chinese medicine treatment on depressive symptoms in elderly patients with alcohol dependence. Methods: Sixty patients were randomly divided into two groups. One group was treated by a set of emotional therapy of Chinese medicine treatment for 12 weeks (control group). One group was treated by a set of acupuncture combined with emotional therapy of Chinese medicine treatment for 12 weeks (treatment group). We compared the curative effect between the control group and the treatment group, the mean alcohol consumption, the SF-36 scores before and after treatment, and the scores of Hamilton Depression Scale before and after treatment of 3, 6, and 9 weeks. Results: Based on the cognitive behavior model, the characteristics and psychological mechanism of depression in elderly patients with alcohol dependence under the COVID-19 epidemic situation were summarized. The total effective rate of the control group was 60%, and that of the treatment group was 100% (p < 0.05). The alcohol consumption of the patients in each group decreased significantly after treatment (p < 0.05), and there was no significant difference in alcohol consumption between the treatment group and the control group (p > 0.05). After 12 weeks of treatment, there were significant differences in PF, RF, physical pain, general health status, energy, and mental health between the treatment group and the control group (p < 0.05). Before and after treatment, there were significant differences in PF, RF, physical pain, general health, energy, emotional function, and mental health (p < 0.05) of the treatment group. The PF, energy, and mental health of the control group were significantly different before and after treatment (p < 0.05). There was no significant difference between the treatment group and the control group in the scores of Hamilton Depression Scale before treatment. There was significant difference between the treatment group and the control group in the scores of Hamilton Depression Scale at 3, 6, and 9 weeks after treatment. Conclusion: Attention, cognition, emotion, behavior, and physical response reinforce each other, creating a vicious cycle that reinforces and sustains the depressive symptoms of elderly alcohol dependence under the COVID-19 epidemic, and acupuncture combined with emotional therapy of Chinese medicine treatment for improving the depressive symptoms of elderly alcohol dependence during the epidemic period of COVID-19 has a brilliant therapeutic effect.